Ecosystem-Based Approaches to Bioenergy and the Need for Regenerative Supply Options for Africa - Duguma, L.; Kamwilu, E.; Minang, Peter A.; Nzyoka, J.; Muthee, K. (MDPI, 2020)
Energy supply systems in the tropics and subtropics are marred with considerable negative impacts on ecosystems, for example, forest loss and habitat destruction. This document examines the role of ecosystems in household energy supply in Africa and explores pathways to ecosystem-based approaches to bioenergy generation by building on the regenerative economy concept. An ecosystem-based approach to bioenergy is an energy supply and utilization mechanism aimed at enhancing sustainable management of the sources of ecosystems with minimal trade-offs on/from other sectors directly linked to energy issues. Our analysis revealed that about 87% of energy supply to the population originated from agroecosystems and is challenged by the severe ecosystem degradation happening due to natural and anthropogenic factors. However, ecosystem restoration and effective use of agricultural residues could provide hope for making energy supply sustainable. Our analysis showed that restoring sparsely vegetated areas and degraded forest and savannahs, promotion of agroforestry in degraded agricultural lands, and use of agricultural residues could generate close to 71 billion gigajoules (GJ) of energy and provide sufficient energy for about 2.5 billion people if implemented in all potential areas identified. Ecosystem-based approaches to bioenergy along with a well-balanced involvement of sectors and industry actors coupled with knowledgeable management of the ecosystem could lead to beneficial outcomes for the society and environment.